Seeing a broader picture: The framework of environmental (in)justice - Nola, Iskra Alexandra; Premec, Ian Renei (Crisis Management Days, 2024)
Introduction: Environmental justice is a critical concept that addresses the unequal distribution of environmental benefits and burdens among different social groups (United Nations 2021). While environmental justice has gained significant attention in recent decades, its scope extends beyond just the fair treatment of communities in environmental decision-making processes. Specifically, it is important in the context of disasters: their raising number related to the climate and social changes and their severity. Even though the environmental justice is in modern world incorporated into policies, the proper extend is still missing (Brulle and Pellow 2017). To explore the framework of environmental justice, delving into its historical context, key principles, contemporary challenges, and implications for policy and advocacy is crucial to understand the future problems raising in disasters. Historical Context: The roots of environmental justice can be traced back to the civil rights movement of the 1960s in the United States. During this time, marginalized communities, particularly African American and low-income neighborhoods, began to mobilize against environmental injustices such as the siting of hazardous waste facilities in their neighborhoods. The landmark case of Warren County, North Carolina, where protests erupted over the siting of a PCB landfill in a predominantly African American community, brought national attention to the issue (Bullard and Johnson 2020). This event catalyzed the environmental justice movement and laid the groundwork for future advocacy efforts. Key Principles: At its core, environmental justice is guided by principles of equity, fairness, and inclusivity. It emphasizes the right of all individuals and communities to a healthy environment, regardless of race, ethnicity, income, or social status. Environmental justice advocates argue that marginalized communities often bear a disproportionate burden of environmental pollution and degradation due to systemic inequalities and discriminatory practices. However, the efforts of the developed world aimed at reducing environmental pollution by introducing regulatory principles and alternative energy sources do not spread evenly to underdeveloped neighborhoods, and it is only a matter of time when this pollution will become a problem for the underdeveloped for whom new technologies are still unavailable. Therefore, achieving environmental justice requires addressing underlying social, economic, and political factors that perpetuate environmental inequities (Bullard and Johnson 2020, Mohai and Saha 2015). Contemporary Challenges: Despite progress in raising awareness about environmental justice issues, significant challenges persist. One major challenge is the intersectionality of environmental injustices with other forms of inequality, such as racial discrimination, economic disparity, and unequal access to resources, and overall – the strength of populations to deal with incoming disasters related to environmental changes and injustice. Additionally, the globalization of environmental issues has led to concerns about environmental colonialism, where wealthier nations exploit the natural resources of poorer countries, further exacerbating inequalities. Furthermore, the impacts of climate change, including extreme weather events, rising sea levels, and food insecurity, disproportionately affect vulnerable communities, widening existing disparities (Gee and Payne-Sturges 2017). Implications for Policy and Advocacy: Addressing environmental justice requires a multifaceted approach that integrates policy interventions, community engagement, and advocacy efforts (United Nations 2021). Policymakers play a crucial role in enacting legislation and regulations that promote environmental equity and protect the rights of marginalized communities (Mohai and Saha 2015, Downey and Hawkins 2016). This includes measures such as environmental impact assessments, zoning regulations, and enforcement of environmental laws. Additionally, fostering meaningful community participation in decision-making processes ensures that the voices of affected communities are heard and their concerns are addressed. Civil society organizations and grassroots movements also play a vital role in advocating for environmental justice, mobilizing communities, raising awareness, and holding institutions accountable for their actions. Conclusion: In conclusion, the framework of environmental justice provides a lens through which to understand and address the unequal distribution of environmental benefits and burdens. By recognizing the interconnectedness of social, economic, and environmental factors, environmental justice advocates seek to create more equitable and sustainable societies. However, achieving environmental justice requires concerted efforts from policymakers, community leaders, activists, and individuals alike. It is important to address systemic inequalities, vulnerable populations, and promote environmental equity, to create a healthier and more just world with resilient populations.